2013
DOI: 10.1002/ppap.201300101
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Uniform Large-Area VHF Plasmas by Launching a Traveling Wave

Abstract: An innovative technique, i.e., creating a traveling wave by launching two specific standing waves at the same time, is proposed to generate uniform large‐area very high frequency (VHF) plasmas. The viability of this approach has been verified by numerical simulation in this study. The electric field distribution for each standing wave is controlled by the phase difference between the corresponding two feeding points (φ) placed on opposite sides of electrode and designated to produce a specific standing wave pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Both experimental [19][20][21] and numerical [22][23][24] research indicated that by varying the phase difference between the two sources applied to the top and bottom electrodes, i.e., the so-called phase-shift control, the plasma currents redistributed and therefore the plasma uniformity could be optimized. Moreover, Chen et al pointed out that the plasma nonuniformity decreased significantly by launching a traveling wave, which was generated by the superposition of two standing waves with the same amplitude and out of phase by 90 • in space and time [25][26][27]. Bera et al introduced the electric potential and the magnetic vector potential to calculate the ES field and the EM field, respectively, and they presented different electron density distributions with various combinations of powers at 60 MHz and 180 MHz [28].…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental [19][20][21] and numerical [22][23][24] research indicated that by varying the phase difference between the two sources applied to the top and bottom electrodes, i.e., the so-called phase-shift control, the plasma currents redistributed and therefore the plasma uniformity could be optimized. Moreover, Chen et al pointed out that the plasma nonuniformity decreased significantly by launching a traveling wave, which was generated by the superposition of two standing waves with the same amplitude and out of phase by 90 • in space and time [25][26][27]. Bera et al introduced the electric potential and the magnetic vector potential to calculate the ES field and the EM field, respectively, and they presented different electron density distributions with various combinations of powers at 60 MHz and 180 MHz [28].…”
Section: Introductionmentioning
confidence: 99%